א"ב יהושע - רטרוספקטיבה: ממטאפיזיקה של רוע לאתיקה של מצבים - ליפסקר-אלבק אבידב (מכאן, 2014)
This article summarizes the literary path taken by writer A.B. Yehoshua from his short stories in the 1960s up to his late novels in the early 21st century. The main argument presented here is that Yehoshua’s early writings establish a stable situation of a “narrating subject” who had lost his main attribute of “writing subject.” This moment of loss is the instant of establishing the story’s fictional world (in terms of space, time, and plot). It is this moment that Yehoshua sets as the Archimedean point from which his obedient subjects generate the plots. For Yehoshua, the absence of a writing authority or the disappearance of a writing entity are an expression of his evil "cosmic entropy,” which is a recurring phobia in his stories. Release from this phobia is only possible when the hero gathers the strength to go on the journey and gets his surroundings to return his lost writing to him. In Yehoshua’s early writings, such journeys are not successful. Yehoshua generated two poetic moves to dismantle evil in his novellas and novels. First, he sealed the mouths of his despotic heroes who are devoid of subject; second, he granted himself complete poetic freedom of invention. In other words, he silenced the voice of the first-person narrator and wrote texts by an author who tells us about his characters, or determines their speech boundaries. By constructing arbitrary, surprising poetics, and reinventing it time after time, he established for himself a position of freedom to be a moral judge of his fictional world and formed a dimension of freedom and ruling in it.